1968
DOI: 10.1017/s0003356100026295
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary consumption of forage by sheep and its relation to the size and shape of particles in the digestive tract

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0003356100026295 How to cite this article: J. E. Troelsen and J. B. Campbell (1968). Voluntary consumption of forage by sheep and its relation to the size and shape of particles in the digestive tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 5 publications
4
36
0
Order By: Relevance
“…Differences in fracture patterns of grass and browse have been noted (Spalinger et al 1986;Kay 1993;Van Wieren 1996a). Several authors have reported more polygonal particles from herbaceous forage leaves and more longish particles from grass leaves (Troelsen and Campbell 1968;Moseley and Jones 1984;Mtengeti et al 1995). Although empirical studies are lacking, browse is thought to be a more heterogeneous material with different levels of tissue thicknesses and of resistance to breakage, whereas grass is considered more homogenous in this respect.…”
mentioning
confidence: 99%
“…Differences in fracture patterns of grass and browse have been noted (Spalinger et al 1986;Kay 1993;Van Wieren 1996a). Several authors have reported more polygonal particles from herbaceous forage leaves and more longish particles from grass leaves (Troelsen and Campbell 1968;Moseley and Jones 1984;Mtengeti et al 1995). Although empirical studies are lacking, browse is thought to be a more heterogeneous material with different levels of tissue thicknesses and of resistance to breakage, whereas grass is considered more homogenous in this respect.…”
mentioning
confidence: 99%
“…Since then a number of other workers have added to this basic information (e.g. Magee, 1932;Balch, 1949Balch, , 1958Balch & Kelly, 1950;Nichols, 1959;Campling & Freer, 1962;Welch, 1965;Pearce, 1967;Troelsen & Campbell, 1968).The rate of passage of digesta through the reticulo-rumen and the rate of breakdown of digesta in that organ are important determinants of the efficiency of digestion and of the rate of rumen emptying (Balch, 1950). Both rate of passage and rate of breakdown appear to be markedly influenced by the physical characteristics of the digesta.…”
mentioning
confidence: 99%
“…The consumption of coarse roughage (Troelsen and campbell, 1968) is directly affected by its rate of physical breakdown dtning mastication and its rate of passage through the reticulo-omasal opening (Balch and Campling, 1965;Troelsen and Bigsby, 1964;Troelsen et al, l97O (Blaxter and wilson, 1962;Greenhalgh and Runcie, 1962;corbett et aI., 1963 …”
Section: Discussionmentioning
confidence: 99%
“…"Coarse roughage" was defined by Troelsen and Campbell (1968) as forage of a quality and texture which will render its rate of passage and voluntary consumption by ruminants dependent on its rate of breakdown by mastication and fermentation in the reticulo-rumen. According to Blaxter (1950), it will be eaten by cattle and sheep at a rate directly proportionali to its concentration of digestible nutrients.…”
mentioning
confidence: 99%